Individual acid aspartic proteinases (Saps) 1-6 of Candida albicans are not essential for invasion and colonization of the gastrointestinal tract in mice - Kretschmar, Marianne; Felk, Angelika; Staib, Peter; Schaller, Martin; Heß, Daniela; Callapiña, Melvin; Morschhäuser, Joachim; Schäfer, Wilhelm; Korting, Hans Christian; Hof, Herbert; Hube, Bernard; Nichterlein, Thomas (Microbial pathogenesis, 2002)
In order to investigate whether there is a role for individual secreted aspartic proteinases (Saps) ofCandida albicans in gastrointestinal infection of mice we compared the differential expression of SAP1-6 genes and production of Sap1-6 proteins with invasion and persistence of SAP knockout strains in the gastrointestinal tract. Using an in vivo expression technology (IVET) we found a high percentage of expression of SAP4-6 genes which increased steadily in the course of infection. Expression of SAP1-3 genes was detected occasionally and in lower percentages than that of SAP4-6 genes. With reverse transcriptase-polymerase chain reaction (RT-PCR), mRNA forSAP 4 and SAP6 were detected in the stomach of all mice, whereas SAP2, SAP3 and SAP5 mRNA were detected not in all animals and SAP1 mRNA was not detectable. Also with immunoelectron microscopy we demonstrated production of Saps1-3 as well as Saps4-6 with antibodies cross-reacting with either Saps1-3 or Saps4-6. In contrast to the fact that gene expression and production of Saps were readily detectable, we were unable to demonstrate differences in the ability to invade the stomach, to disseminate to the brain as well as in the duration of faecal shedding and the number of fungi persisting in the faeces of mice infected with SAP knockout strains in comparison to control strains. We conclude that although Saps were produced, individual Saps were not indispensable factors for virulence during gastrointestinal infection of mice.